Prototype Alat Pengamanan Pintu dengan Menggunakan Sensor Sidik Jari Berbasis Arduino Mega2560 - Rudi Handika; Dedy Hartama; Ika Okta Kirana; M. Safii; Iin Parlina (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
The door is the most important and important part of a room to pay attention to its safety compared to other parts because it is from the door that everyone will enter or leave. This study aims to build a door security device using a Fingerprint sensor based on Arduino Mega 256. The door that will be given a security device is the door in classes at STIKOM Tunas Bangsa Pematangsiantar. This tool can be used as a security control system at the classroom door, users do not need to use manual security such as keys, and this tool is also equipped with an alarm as a marker when the Fingerprint sensor is accessed by someone who is not the owner, this alarm will sound. This system consists of hardware and Software. The hardware consists of an Arduino Uno, Fingerprint sensor, buzzer, Selenoid door, LCD and then the Software on this system uses the Arduino IDE program. This system runs if the Fingerprint sensor detects a finger from the user, the solenoid as a door lock will open. Otherwise, if the sensor does not see a finger from the user, the solenoid as a door lock will not open, and an alarm will sound. This door safety device can effectively be used as security on classroom doors and other rooms such as leadership rooms, education rooms and staff rooms